The reality of career and teacher development as an EAP practitioner - an outsider's view looking in. - Hudson, Alexandra (2015)
The field of English for Academic Purposes (EAP) has been expanding in recent years, due to increasing numbers of international students wishing to study at UK universities. However, demand is led by student numbers, creating a situation, whereby on the one hand, EAP is a burgeoning academic discipline, whilst on the other hand, it is a commercial activity. It is a dichotomy with clear tensions. This is an exploration into the effects of these tensions on EAP practitioners, examining the situation from the perspective of the practitioners themselves. A narrative inquiry begins, with the researcher’s own personal questions and frustrations. As a sessional lecturer the researcher feels like an outsider looking in at a closed field that is desirable, but difficult to enter. A literature review and interviews with a mix of permanent and sessional lecturers at two different universities were used to compare the findings from the narrative. The picture that emerged was remarkably similar from all sources. Sessionals shared many of the narrative’s frustrations at finding it difficult to enter the profession and ‘luck’ appeared as a key factor in entering the profession. However, a surprising picture also emerged of frustrations from permanent staff at how to develop once in the profession. Many saw research as the only viable way to gain promotion, but did not want to pursue this path as it was teaching that had attracted them to the profession. From the exploration it also emerged that a feeling of community and collaboration amongst staff is important to promote feelings of value and worth, which in turn encourage improved delivery on the part of the teacher. The exploration proposes that short-term contracts, rather than hourly pay should be encouraged. It also suggests more awareness should be raised of what BALEAP1 can offer, at individual and departmental level, as well as awareness raising and promotion of BALEAP’s TEAP fellowship scheme2.